Sulfuric acid compositions and uses thereof

Through the improved aqueous acid-based composition, the low temperature and low pressure delignification of wood is achieved by using the combination of sulfuric acid, ammonia-containing sulfate compounds and peroxides, and the problems of high energy consumption, high equipment costs and serious environmental pollution in the prior art are solved, and efficient and environmentally friendly wood pulp production and biomass conversion process is achieved.

JP7671075B2Active Publication Date: 2025-05-01SIXRING INC
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
JP2022549742
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-02-28
Filing Date
2021-02-26
Publication Date
2025-05-01
Estimated Expiration
2041-02-26

AI Technical Summary

Technical Problem

During the existing wood pulp production and biomass conversion, energy consumption is high, equipment costs are expensive and environmental pollution is severe, especially during the decomposition of lignon and the separation of cellulose fibers.

Method used

Low temperature and low pressure deligification of wood is achieved by controlling its molar ratio (eg, the molar ratio of sulfuric acid: ammonia sulfate compound: peroxide is between 1:1:1 and 15:1:1) using an improved aqueous acid-based composition, including sulfuric acid, ammonia sulfate compound and peroxide.

Benefits of technology

This method can effectively decompose lignin at lower temperatures and pressures, reduce damage to cellulose fibers, reduce energy consumption and equipment costs, and reduce environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007671075000003
    Figure 0007671075000003
  • Figure 0007671075000004
    Figure 0007671075000004
  • Figure 0007671075000005
    Figure 0007671075000005
Patent Text Reader

Abstract

An aqueous acid composition comprising sulfuric acid, a compound comprising an amine moiety and a sulfonic acid moiety, and optionally a peroxide. Use of the composition in biomass treatment is also disclosed.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] TECHNICAL FIELD TO WHICH THEINVENTION BELONGS The present invention relates to methods and compositions useful for the decomposition of organic matter by oxidation, e.g., delignification of wood material, and more particularly to methods and compositions for accomplishing this under more optimal conditions than those currently used in the Kraft process. [Background technology]

[0002] 2. Background of the Invention The largest energy consumer in paper production is the production of pulp. Wood and other plants from which pulp is made contain three main components: cellulose fibers, lignin, and hemicellulose, as well as water. The primary objective of pulping is to separate the fibers and lignin. Lignin is a three-dimensional polymer that acts as a kind of mortar that holds all the fibers together in the plant. Lignin is undesirable in pulp and does not add anything to the final product. Wood pulping involves breaking down the bulk structure of fibrous raw materials, such as chips, stems, and other plant parts, into their constituent fibers. Cellulose fibers are the most important component in the papermaking process. Hemicellulose is a shorter branched carbohydrate polymer made up of various sugar monomers randomly arranged in an amorphous polymeric structure. The presence of hemicellulose in the finished pulp is not as important for the stiffness of the paper as cellulose. This is also true for biomass conversion. The challenges are similar; the desired results are different. In biomass conversion, further degradation to monovalent carbohydrates is the desired outcome, but in pulp and paper processes this is usually stopped soon after lignin dissolution.

[0003] There are two main approaches to the preparation of wood pulp or woody biomass: mechanical and chemical processing. Mechanical processing or pulping generally aims to physically tear the wood chips, thus splitting the cellulose fibers and separating them from each other. The disadvantages of this method are that the cellulose fibers are cut or damaged, resulting in shorter fibers, and that lignin is mixed or left in the cellulose fibers, resulting in impurities in the final product. The process is also energy-intensive and capital-intensive, since it requires high pressure, caustic chemicals, and heat. There are several approaches and processes for chemical pulping. These generally focus on breaking down the lignin and hemicellulose into water-soluble molecules. These broken down components are separated from the cellulose fibers by washing, without damaging the cellulose fibers. This chemical process is energy-intensive, since it requires a large amount of heat, and also often requires stirring and mechanical intervention, which increases the inefficiency and cost of the process.

[0004] Pulping or processing methods exist that combine the chemical aspects of pulping with the mechanical aspects of pulping to various degrees. Examples include thermomechanical pulping (also commonly referred to as TMP), chemi-thermo-mechanical pulping (CTMP), etc. By selecting the advantages offered by each common pulping method, the process is performed to reduce the amount of energy required for the mechanical aspects of the pulping process. This can also have a direct impact on the degradation of strength or tensile strength of fibers subjected to these combined pulping approaches. In general, these approaches shorten the chemical treatment (compared to traditional dedicated chemical pulping) and usually follow it with a mechanical treatment to separate the fibers.

[0005] The most common method of producing pulp for papermaking is the Kraft process. In the Kraft process, wood chips are converted into wood pulp, which is almost pure cellulose fiber. The Kraft process begins by impregnating and treating the wood chips with white liquor, a strong alkaline chemical solution containing sodium hydroxide and sodium sulfide. This is done by soaking the wood chips and then heating them with steam. This process causes the wood chips to expand, and the air inside the wood chips is removed and replaced by white liquor. The wood material is soaked in various chemical solutions and then cooked. To delignify the wood chips, they are heated at temperatures that reach 176°C for several hours. At this temperature, the lignin is broken down and water-soluble fragments are produced. At this time, black liquor is generated as a by-product of the Kraft process. Black liquor contains water, lignin residues, hemicellulose, and inorganic chemicals. The remaining cellulosic fibers are collected and washed after the cooking process.

[0006] U.S. Patent No. 5,080,756 teaches an improved kraft pulping process, characterized in that a spent concentrated sulfuric acid composition containing organic matter is added to a kraft recovery system to provide a mixture enriched in its total sulfur content which is subjected to dehydration, pyrolysis and reduction in a recovery furnace. The organic matter of the sulfuric acid composition is particularly useful as a source of thermal energy that can easily maintain high heat levels to promote the oxidation and reduction reactions that occur in the furnace, resulting in the formation of sulfides which are used to prepare a cooking liquor suitable for pulping.

[0007] Caro's acid, also known as peroxymonosulfuric acid (H2SO5), is one of the strongest oxidizing agents known and highly explosive. Several reactions are known for the preparation of Caro's acid, but one of the simplest involves the reaction of sulfuric acid (H2SO4) with hydrogen peroxide (H2O2). Once prepared in this manner, Caro's acid can be further reacted to prepare potassium monopersulfate (PMPS), a valuable bleaching and oxidizing agent. Caro's acid has several known useful applications, most notably in wood delignification.

[0008] Peracetic acid, as well as Caro's acid, form flammable vapors and liquids with sulfuric acid (35%). Therefore, when reactions involving such mixtures are heated, the presence of flammable materials and strong oxidizers is likely to be present, which is a major safety concern and can lead to explosions. The use of such reactive materials is not welcomed in large-scale applications due to their unacceptable risk profile. The safety concerns are much the same, as Caro's acid and peracetic acid (with sulfuric acid) are corrosive and strong oxidizers.

[0009] Biofuel production is also a potential application of the Kraft process. A current drawback of biofuel production is the need to use food-grade plant parts (such as seeds) to convert carbohydrates into fuel in a reasonably efficient process. Carbohydrates can also be obtained from cellulosic fibers by using non-food-grade biomass in the Kraft process, but the Kraft process is energy-intensive for delignification, making it a less commercially viable option. To build a plant-based chemical resource cycle, there is a great need for energy-efficient processes that can utilize plant-based feedstocks that do not compete with human food production.

[0010] The kraft pulping process is the most widely used chemical pulping process in the world, but it is very energy intensive and has drawbacks, such as a significant odor around the pulping plant and general emissions that are currently heavily regulated in many paper pulp manufacturing jurisdictions. In view of current environmental concerns resulting from climate change and emissions fees or taxes that are being implemented, there is a strong desire to optimize current pulping processes to economically provide high quality fiber without adversely affecting the environment during its production. Thus, there is a need for compositions that can perform delignification on wood materials at lower temperatures and pressures than those currently used, without requiring significant additional capital expenditures. Summary of the Invention

[0011] Summary of the Invention In accordance with one aspect of the present invention, there is provided a modified aqueous acid composition comprising: Sulfuric acid; Compounds containing an amine moiety and a sulfonic acid moiety; and Peroxide; Including, A modified aqueous acid composition wherein sulfuric acid, said compound comprising an amine moiety and a sulfonic acid moiety, and said peroxide are present in a molar ratio of not less than 1:1:1.

[0012] According to a preferred embodiment, the sulfuric acid, the compound comprising an amine moiety and a sulfonic acid moiety, and the peroxide are present in a molar ratio not exceeding 15:1:1.

[0013] In accordance with another aspect of the present invention, there is provided a denatured acid composition comprising: Sulfuric acid; Compounds containing an amine moiety and a sulfonic acid moiety; Including, wherein the sulfuric acid and the compound comprising an amine moiety and a sulfonic acid moiety are present in a molar ratio of 3:1 or greater.

[0014] Preferably, the compound comprising an amine moiety and a sulfonic acid moiety is selected from the group consisting of taurine; taurine derivatives; and taurine-related compounds. Also preferably, the taurine derivative or taurine-related compound is selected from the group consisting of sulfamic acid; taurolidine; taurocholic acid; taurocercholic acid; tauromustine; 5-taurinomethyluridine and 5-taurinomethyl-2-thiouridine; homotaurine (tramiprosate); acamprosate; and taurate; and aminoalkylsulfonic acids in which alkyl is selected from the group consisting of C1-C5 linear alkyl and C1-C5 branched alkyl. Preferably, the linear alkyl aminosulfonic acid is selected from the group consisting of methyl; ethyl (taurine); propyl; and butyl. Preferably, the branched aminoalkylsulfonic acid is selected from the group consisting of isopropyl; isobutyl; and isopentyl.

[0015] Most preferably, the compound containing an amine moiety and a sulfonic acid moiety is taurine.

[0016] According to a preferred embodiment, the sulfuric acid and the compound comprising an amine moiety and a sulfonic acid moiety are present in a molar ratio of 3:1 or greater.

[0017] According to another aspect of the present invention, there is provided an aqueous composition comprising: 1. An aqueous composition for use in delignification of wood or wood pulp, comprising: Sulfuric acid, 20-70 wt%; A compound containing an amine moiety and a sulfonic acid moiety selected from the group consisting of taurine; taurine derivatives; and taurine-related compounds; and Peroxide; The composition comprising:

[0018] Preferably, the composition has a pH of less than 1, and more preferably, the composition has a pH of less than 0.5.

[0019] According to a preferred embodiment of the present invention, there is provided the following composition: 1. A composition for use in wood delignification, comprising: Sulfuric acid 40-80 wt%; A compound containing an amine moiety and a sulfonic acid moiety selected from the group consisting of taurine and its derivatives (such as taurine-related compounds); Including, wherein the sulfuric acid and the amine-containing compound are present in a molar ratio ranging from 3:1 to 15:1.

[0020] Preferably, the taurine derivative or taurine related compound is selected from the group consisting of: taurolidine; taurocholic acid; taurocercholic acid; tauramustine; 5-taurinomethyluridine and 5-taurinomethyl-2-thiouridine; homotaurine (tramiprosate); acamprosate; and taurate.

[0021] According to another aspect of the present invention, there is provided an aqueous composition comprising: 1. An aqueous composition for use in degrading or separating cellulose from a plant source, comprising: Sulfuric acid, 20-70 wt%; A compound comprising an amine moiety and a sulfonic acid moiety selected from the group consisting of taurine; taurine derivatives; and taurine-related compounds, Peroxide; Including, wherein said sulfuric acid and said amine-containing compound are present in a molar ratio ranging from 3:1 to 15:1.Preferably, said compound containing an amine moiety and a sulfonic acid moiety is taurine.

[0022] According to a preferred embodiment of the present invention, the peroxide is hydrogen peroxide.

[0023] According to another aspect of the present invention, there is provided a method comprising: 1. A method for delignification of plant material comprising the steps of: - providing said biomass material comprising cellulose fibers and lignin; - the biomass material required, Sulfuric acid, 20-70 wt%; A compound containing an amine moiety and a sulfonic acid moiety selected from the group consisting of taurine; taurine derivatives; and taurine-related compounds; and a peroxide; for a time sufficient to remove substantially all of the lignin present on the biomass material; The method comprising:

[0024] Taurates are used as mild, high-foaming surfactants in body cleansers and personal care products, as wetting agents, detergents, dye dispersants in textile processing, crop protection formulations and other industrial applications.

[0025] The inventors have discovered that delignification of wood materials (e.g., but not limited to, wood chips or other common biomass) can occur at temperatures substantially lower than those used during conventional kraft pulping. Indeed, several experiments have been performed with the preferred composition at average room temperatures ranging from 18 to 21°C, which show that the present invention decomposes the lignin present on the wood chips to liberate cellulose fibers very efficiently. According to another preferred embodiment of the method according to the present invention, wood samples were dissolved at 30°C upon exposure to the composition according to the preferred embodiment of the present invention. According to a preferred embodiment of the present invention, the energy costs, the capital costs involved, and the associated emissions currently discharged in pulp delignification can be significantly reduced by applying a method including the preferred composition of the present invention. According to another preferred embodiment of the method according to the present invention, biomass can be dissolved at 0°C upon exposure to the preferred composition of the present invention.

[0026] In accordance with a preferred embodiment of the present invention, a multi-step process is provided that relies on time, temperature and molar ratios of the preferred compositions of the present invention, where separate steps of dissolution achieve: 1. Delignification; 2. Dissolution of hemicellulose; and 3. Dissolution of crystalline cellulose. [Brief description of the drawings]

[0027] Brief description of the drawings The present invention may be more fully understood in consideration of the following description of various embodiments of the invention in conjunction with the accompanying drawings, in which: FIG. [Figure 1-6]FIG. 1 is a photograph comparing the dissolution of wood chips in sulfuric acid (right beaker) with the composition according to the present invention (left beaker) over a period of 1 minute. FIG. 2 is a photograph comparing the dissolution of wood chips in sulfuric acid in the presence of peroxide (right beaker) with the composition according to the present invention in the presence of peroxide (left beaker) over a period of 1 minute. FIG. 3 is a photograph comparing the dissolution of wood chips in sulfuric acid (right beaker) with the composition according to the present invention (left beaker) over a period of 8 minutes. FIG. 4 is a photograph comparing the dissolution of wood chips in sulfuric acid in the presence of peroxide (right beaker) with the composition according to the present invention in the presence of peroxide (left beaker) over a period of 5 minutes. FIG. 5 is a photograph comparing the dissolution of wood chips in sulfuric acid (right beaker) with the composition according to the present invention (left beaker) over a period of 16 minutes. FIG. 6 is a photograph comparing the dissolution of wood chips in sulfuric acid in the presence of peroxide (right beaker) with the composition according to the present invention in the presence of peroxide (left beaker) over a period of 10 minutes. [Figure 7-12] FIG. 7 is a comparative photograph of dissolution of wood chips in sulfuric acid (right beaker) and a composition according to the invention (left beaker) after 26 minutes. FIG. 8 is a comparative photograph of dissolution of wood chips in sulfuric acid in the presence of peroxide (right beaker) and a composition according to the invention (left beaker) after 15 minutes. FIG. 9 is a comparative photograph of dissolution of wood chips in sulfuric acid (right beaker) and a composition according to the invention (left beaker) after 39 minutes. FIG. 10 is a comparative photograph of dissolution of wood chips in sulfuric acid in the presence of peroxide (right beaker) and a composition according to the invention (left beaker) after 25 minutes. FIG. 11 is a comparative photograph of dissolution of wood chips in sulfuric acid (right beaker) and a composition according to the invention (left beaker) after 44 minutes. FIG. 12 is a comparative photograph of the dissolution of wood chips in sulfuric acid in the presence of peroxide (right beaker) and a composition according to the invention in the presence of peroxide (left beaker) over a period of 40 minutes. [Figure 13-14]Figure 13 is a comparative photograph of the dissolution of wood chips in sulfuric acid (right beaker) and a composition according to the invention (left beaker) after 60 minutes. Figure 14 is a comparative photograph of the dissolution of wood chips in sulfuric acid in the presence of peroxide (right beaker) and a composition according to the invention in the presence of peroxide (left beaker) after 60 minutes. [Figure 15] 15a-15h are a series of photographs showing chicken skin exposed to a conventional Caro's acid composition for up to 45 minutes; and [Figure 16] 16a-16i are a series of photographs showing chicken skin exposed to a modified Caro's acid composition according to a preferred embodiment of the present invention for up to 75 minutes. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0028] Detailed Description of the Invention Experiments carried out with aqueous acidic compositions according to preferred embodiments of the present invention have revealed that woody biomass can be delignified under controlled reaction conditions, eliminating or at least minimizing the degradation of cellulose, where degradation is understood to mean the blackening or charring of cellulose (conversion to carbon black), which is emblematic of the uncontrolled acid attack of cellulose and its staining.

[0029] Preferably, the composition according to the invention comprises: Sulfuric acid; and A compound comprising an amine moiety and a sulfonic acid moiety selected from the group consisting of taurine; taurine derivatives and taurine related compounds.

[0030] Preferably, taurine derivatives and taurine related compounds are understood to include sulfamic acid, taurolidine, taurocholic acid, tauroserucholic acid, tauramustine, 5-taurinemethyluridine and 5-taurinemethyl-2-thiouridine, homotaurine (tramiprosate), acamprosate, and taurates, as well as aminoalkylsulfonic acids, the alkyl of which is selected from the group consisting of C1-C5 straight chain alkyl and C1-C5 branched alkyl. Preferably, the straight chain alkyl aminosulfonic acid is selected from the group consisting of methyl, ethyl (taurine), propyl, and butyl. Preferably, the branched aminoalkylsulfonic acid is selected from the group consisting of isopropyl, isobutyl, and isopentyl.

[0031] According to a preferred embodiment, the taurine derivatives and taurine-related compounds are selected from the group consisting of: taurolidine; taurocholic acid; taurocercholic acid; tauromustine; 5-taurinomethyluridine and 5-taurinomethyl-2-thiouridine; homotaurine (tramiprosate); acamprosate; and taurate.

[0032] Most preferably, the compound containing an amine moiety and a sulfonic acid moiety is taurine.

[0033] When wood delignification is carried out using compositions according to preferred embodiments of the invention, the process can be carried out at temperatures substantially lower than those used in conventional kraft pulping processes. The advantages are considerable, some of which are listed here: current kraft pulping processes require temperatures around 176-180°C to carry out the delignification step, but preferred embodiments of the process according to the invention are capable of delignifying wood at much lower temperatures, even as low as 20°C. According to preferred embodiments of the invention, wood delignification can be carried out at temperatures as low as 0°C. According to preferred embodiments of the invention, wood delignification can be carried out at temperatures as low as 10°C. According to preferred embodiments of the invention, wood delignification can be carried out at temperatures as low as 30°C. According to another preferred embodiment of the invention, wood delignification can be carried out at temperatures as low as 40°C. According to yet another preferred embodiment of the invention, wood delignification can be carried out at temperatures as low as 50°C. According to yet another preferred embodiment of the invention, wood delignification can be carried out at temperatures as low as 60°C.

[0034] In each one of the above preferred embodiments, the temperature at which the process is carried out is substantially lower than current energy intensive and inefficient kraft processes.

[0035] Additionally, the Kraft process uses high pressure to initially perform wood delignification which is capital intensive, dangerous, expensive to maintain, and has high associated turnaround or maintenance costs. In accordance with preferred embodiments of the present invention, wood delignification can be performed at atmospheric pressure. This, in turn, avoids the need for highly specialized and expensive industrial equipment such as pressure vessels / digestors. It also allows for the implementation of delignification units in many parts of the world where the implementation of Kraft plants was previously unfeasible for a variety of reasons.

[0036] Some of the advantages of the process according to the preferred embodiment of the present invention over the conventional kraft process are substantial, as the heat / energy requirements for the latter are not only a major source of pollution, but are a large part of the reason why the resulting pulp product is so expensive and has high initial capital requirements. The energy savings in implementing the process according to the preferred embodiment of the present invention will be reflected in a lower cost pulp, and the environmental benefits will have both immediate and long-term multi-generational benefits for everyone.

[0037] Further cost savings in the full or partial implementation of a process according to a preferred embodiment of the present invention can be found in the absence or minimization of restrictive regulations on the operation of the high temperature and high pressure pulp digester.

[0038] Example 1 The composition according to the preferred embodiment of the present invention used in the delignification test was prepared by dissolving one molar equivalent of taurine in sulfuric acid, followed by the addition of hydrogen peroxide. The final composition is composed of sulfuric acid:taurine:hydrogen peroxide in a molar ratio of 5:1.7:1.0. Preferably, the resulting pH of the composition is less than 1, more preferably, the resulting pH of the composition is less than 0.5.

[0039] According to a preferred embodiment of the present invention, the composition provides a peroxide yield of greater than 25% 7 days after mixing the composition. More preferably, the percent peroxide yield is greater than or equal to 35% 2 weeks after mixing the composition.

[0040] Delignification experiment A preferred embodiment of the composition according to the present invention was tested to determine its ability in delignifying wood chips.

[0041] Experiments were completed using approximately 0.2 g of wood and approximately 20 g of solution. The mixture was stirred at 200 rpm at a temperature of 30°C.

[0042] Figures 1, 3, 5, 7, 9, 11 and 13 compare the dissolution of wood chips in the presence of sulfuric acid (right beaker in all pictures) with a composition according to a preferred embodiment of the present invention (left beaker in all pictures), which contains sulfuric acid and taurine in a ratio of 3:1. It is noteworthy to point out that right beaker showed evidence of active oxidation to produce carbon black from the very beginning of the experiment. This indicates that sulfuric acid not only breaks down the lignin contained in the wood chips, but also breaks down the cellulosic material quite rapidly to produce carbon black. This effect continues throughout the experiment up to 60 minutes. In the left beaker, the solution gradually darkens, also evidence of the decomposition of the cellulosic material to carbon black, but the reaction slows down significantly and the solution becomes very light in color at 8 minutes. If you look closely, you will see that even at 16 minutes, the color change is still lighter than the sulfuric acid only solution at 1 minute.

[0043] Figures 2, 4, 6, 8, 10, 12 and 14 compare the dissolution of wood chips in the presence of sulfuric acid and hydrogen peroxide (right beaker in all pictures) with a composition according to a preferred embodiment of the invention that also contains hydrogen peroxide (left beaker in all pictures). After 1 minute, it is observed that the sulfuric acid / hydrogen peroxide solution is still fairly clear, although some coloration begins to appear. This coloration is indicative of carbon black remaining in the solution. In the beaker containing the preferred composition of the invention, the solution is clear even after 1 minute. In fact, even after 60 minutes, the solution of the preferred embodiment remains clear. As for the sulfuric acid beaker, the solution darkens somewhat at 5 minutes and does not appear to deteriorate any further from that point on.

[0044] The above experiments clearly demonstrate that the compositions according to the present invention not only provide adequate dissolving acid to delignify plant material, but are also valuable in controlling the ultimate breakdown of cellulosic material into carbon black residues, resulting in higher yields for operators, thus increasing profitability while reducing emissions and risks to employees, contractors and the public.

[0045] A method for obtaining glucose from wood pulp would represent a significant advance over current processes where such conversion is chemically, energy, and emissions intensive, costly, and hazardous while not producing highly efficient results, especially in large-scale operations. It would be desirable to employ a composition that can delignify wood pulp, but also provide some control to the operator to preserve cellulose rather than decompose it into carbon black, in order to improve efficiency and yield, increase safety, and reduce overall costs.

[0046] According to a preferred embodiment of the method of the present invention, separation of lignin can be achieved and the resulting cellulose fibers can be further processed to obtain glucose monomers. Glucose chemistry has numerous applications as a starting block for the preparation of widely used chemicals including, but not limited to, diacetonides, dithioacetals, ethanol, glucosides, glucals and hydroxyglucals.

[0047] Further delignification experiments Sulfuric acid, taurine and hydrogen peroxide were mixed to give low taurine concentrations and reacted with biomass (wood chips) overnight at room temperature to evaluate the effect of changing the molar ratio on the extent of reaction. Control studies were also performed with mixtures in which only kraft lignin or cellulose was added instead of biomass. Commercially available lignin (Sigma-Aldrich; Lignin, kraft; Prod# 471003) was used as a control in the study. Commercially available cellulose (Sigma-Aldrich; Cellulose, fibers (medium); Prod# C6288) was also used as a control in the study.

[0048] The solid phase of each blend was filtered after 20 hours reaction time, washed with water and then dried to constant weight in an oven at 45 °C. All data are the average of three replicate experiments. An effective blend should dissolve all the lignin and leave the cellulose as intact as possible. The experimental results are reported in Table 1 below.

[0049] [Table 1]

[0050] A 3:1:3 molar ratio blend of sulfuric acid (used at 96% concentration):taurine:hydrogen peroxide (as a 30% solution) gave 40% mass recovery from wood, 86% mass recovery from cellulose, and no lignin. All lignin was degraded to the point of being dissolved in the blend. It was noted that reducing the taurine concentration to 10:1:10 or 15:1:15 did not significantly change the solids recovery results. Even at the lowest concentration, taurine is an effective retarder for sulfuric acid, stabilizing the reaction mixture.

[0051] Skin corrosion test To evaluate the immediate corrosiveness of the composition according to the preferred embodiment of the present invention, a visual comparative evaluation was performed using chicken skin. Two chicken skin samples were fixed over the openings of two beakers. The first skin sample was exposed to a solution of sulfuric acid (H2SO4) and hydrogen peroxide (H2O2). The second skin sample was exposed to the composition according to the preferred embodiment of the present invention, i.e., sulfuric acid; taurine; and hydrogen peroxide (H2O2) (molar ratio of 5.0:1.7:1.0).

[0052] Figures 15a-15h (showing skin treated with standard H2SO4-H2O2 solution) show the corrosivity results at times 0, 4, 6, 10, 15, 30 and 45 minutes. Figures 16a-16i (showing skin treated with the above H2SO4-taurine-H2O2 composition) show the corrosivity results at times 0, 5, 10, 15, 30, 45, 60 and 75 minutes. This percutaneous corrosivity test comparison between conventional Caro's acid and (sulfuric acid:taurine molar ratio 3:1) highlights the safety advantage of the composition according to the preferred embodiment of the present invention. The sulfuric acid concentrations in Caro's acid and modified Caro's acid were about 80 wt% and 60 wt%, respectively, while the hydrogen peroxide concentrations were comparable.

[0053] Conventional Caro's acid breaks through after about 5.5 minutes. The modified Caro's acid according to the preferred embodiments described and tested breaks through the skin samples after about 45 minutes, but to a much lesser extent than conventional Caro's acid. Although this is not an official test recognized by the OECD, the test clearly highlights the advantage that a person accidentally exposed to modified Caro's acid according to embodiments of the present invention has significantly more time available to find a safe shower to minimize irreversible skin damage and further damage.

[0054] Titration of Caro's Acid and Preferred Compositions of the Present Invention We have synthesized and titrated both Caro's acid (5.57:1 molar ratio of H2SO4:H2O2) and modified Caro's acid (5.0:1.7:1.0 molar ratio of H2SO4:Taurine:H2O2) using an ice bath and constant stirring. The compositions are stored capped but unsealed in a water bath at a constant temperature of 30°C.

[0055] To determine the concentration of H2O2, the solution was titrated against a standardized KMnO4 solution. The titration procedure is as follows: 1. Prepare a solution of approximately 245 mL of dH2O and 5 mL of 96% H2SO4. 2. Weigh approximately 1 g of Caro's acid / modified Caro's acid on an analytical balance and record. 3. Quantitatively transfer the measured Caro's acid / Corrected Caro's acid to a 300 mL Erlenmeyer flask using the diluted H2SO4 solution. 4. The solution is constantly mixed with a magnetic stir plate / stir bar during the titration. 5. Titrate with standardized KMnO4 solution until a pink color appears that persists for at least 1 minute.

[0056] The percent yield is calculated from the number of moles of H2O2 contained in the titration sample and the number of moles of H2O2 used in the synthesis.

[0057] [Table 2]

[0058] Comparing Caro's acid and modified Caro's acid, modified Caro's acid has significantly higher H2O2 activity after synthesis and retains its activity for a long period of time (at least 27 days), which significantly extends the shelf life of the product, improves work efficiency, and minimizes waste from expired products.

[0059] Batch process - Blend used: H 2 SO 4 :H 2 O 2 :The molar ratio of sulfamic acid is 10:10:1. To scale up the use of the composition according to the preferred embodiment of the present invention in the process as discussed above, a batch process was carried out. To prepare the batch process, 3,301 g of sulfuric acid (93%) was placed in a large glass reactor (nominal volume 10 L) and 304 g of sulfamic acid was added. The mixture was stirred at 100 RPM with an overhead Teflon paddle stirrer. Next, 3,549 g of hydrogen peroxide solution (29%) was added slowly (1-1.5 hours) to the modified acid. The reactor was cooled to dissipate the heat generated so that the temperature of the blend did not exceed 40°C. After the addition of hydrogen peroxide, 846 g of water was added to the mixture and the blend was left to equilibrate to ambient temperature (approximately 30 minutes). The molar blend ratio (order of addition) was 10:1:10. 400 g of unsized wood chips (sawdust) was added slowly (10 minutes) to the reactor. The temperature rise was monitored. When the reactor temperature reached 50°C, the reactor was cooled to a temperature of 26°C. After this, cooling was no longer necessary. After 20 hours of reaction, the reaction mixture was transferred to a filter system with a 20 μm Teflon filter sheet. The filtrate was discarded and the remaining filter cake was washed with 12 liters of water until the effluent had a pH value of about 6. The filter cake was dried overnight in an oven dryer (45°C). The cellulose yield compared to the added biomass was 42.6%.

[0060] The resulting cellulose had a hydrocarbon content of 94.9%, close to the standard Sigma-Aldrich cellulose Lot# WXBC9745V-95.7% used for comparison. The moisture content was 2.22%, close to the standard Sigma-Aldrich cellulose Lot# WXBC9745V-3% used for comparison. The Kappa# = 0 indicates that no lignin remains in the sample. X-ray diffraction showed an apparent crystallinity of 58.2%, consistent with previous testing, and 62.9% for Aldrich commercial cellulose. Scanning electron microscopy showed a higher fiber content than the Sigma-Aldrich product.

[0061] According to another preferred embodiment of the present invention, the composition can be used for decomposition of organic matter by oxidation, such as those used in water treatment, water purification and / or desalination. An example of this is the removal (i.e., destruction) of algae on filtration membranes. Filtration membranes are expensive, so it is desirable to use them as long as possible. However, it is difficult to remove organic matter attached to the membrane, and a new approach is needed to remove it efficiently without damaging the membrane. Mineral acids are too strong, so they can remove organic matter, but they will damage the filtration membrane. The preferred composition of the present invention improves this problem because it is less aggressive than mineral acids, resulting in a much gentler approach to remove organic pollutants, thus sparing the membrane.

[0062] Although the foregoing invention has been described in some detail for purposes of clarity and understanding, it will be understood by those skilled in the relevant art, once familiar with this disclosure, that various changes in form and detail may be made therein without departing from the true scope of the invention as set forth in the appended claims. In relation to the present invention, the following is further disclosed: [1] Sulfuric acid; Compounds containing an amine moiety and a sulfonic acid moiety; and Peroxides, A modified aqueous acid composition comprising: wherein the sulfuric acid, the compound containing an amine moiety and a sulfonic acid moiety, and the peroxide are present in a molar ratio of 1:1:1 or greater. [2] 2. The modified aqueous acid composition of claim 1, wherein sulfuric acid, the compound containing an amine moiety and a sulfonic acid moiety, and the peroxide are present in a molar ratio of 15:1:1 or less. [3] Sulfuric acid; Compounds containing an amine moiety and a sulfonic acid moiety; A denatured acid composition comprising: The composition wherein sulfuric acid and the compound containing an amine moiety and a sulfonic acid moiety are present in a molar ratio of 3:1 or greater. [4] The composition according to any one of [1] to [3], wherein the compound containing an amine moiety and a sulfonic acid moiety is selected from the group consisting of taurine; taurine derivatives; and taurine-related compounds. [5] The composition of [4], wherein the taurine derivative or taurine-related compound is selected from the group consisting of sulfamic acid; taurolidine; taurocholic acid; tauroserucholic acid; tauromustine; 5-taurinomethyluridine and 5-taurinomethyl-2-thiouridine; homotaurine (tramiprosate); acamprosate; and taurates; and aminoalkylsulfonic acids in which the alkyl is selected from the group consisting of C1 to C5 straight chain alkyl and C1 to C5 branched alkyl. [6] The composition of claim 5, wherein the linear alkylaminosulfonic acid is selected from the group consisting of methyl; ethyl (taurine); propyl; and butyl. [7] The composition according to [5], wherein the branched aminoalkyl sulfonic acid is selected from the group consisting of isopropyl; isobutyl; and isopentyl. [8] The composition according to any one of [1] to [4], wherein the compound containing an amine moiety and a sulfonic acid moiety is taurine. [9] The composition according to any one of [1] to [8], wherein the sulfuric acid and the compound containing an amine moiety and a sulfonic acid moiety are present in a molar ratio of 3:1 or more.

[10] 1. An aqueous composition for use in delignification of plant biomass, said composition comprising: sulfuric acid, from 20 to 70 wt. % relative to the total weight of the composition; A compound comprising an amine moiety and a sulfonic acid moiety selected from the group consisting of taurine; taurine derivatives; and taurine-related compounds, Peroxides, The composition comprising:

[11] The composition according to

[10] for use in delignification of plant biomass, the composition comprising: sulfuric acid, from 40 to 80 wt. % relative to the total weight of the composition; A compound comprising an amine moiety and a sulfonic acid moiety selected from the group consisting of taurine and its derivatives (such as taurine-related compounds); Including, The composition, wherein the sulfuric acid and the compound comprising an amine moiety and a sulfonic acid moiety are present in a molar ratio ranging from 3:1 to 15:1.

[12] The composition of any of

[10] and

[11] , wherein the taurine derivative or taurine-related compound is selected from the group consisting of sulfamic acid; taurolidine; taurocholic acid; tauroserucholic acid; tauromustine; 5-taurinomethyluridine and 5-taurinomethyl-2-thiouridine; homotaurine (tramiprosate); acamprosate; and taurate; and aminoalkylsulfonic acids in which alkyl is selected from the group consisting of C1 to C5 straight chain alkyl and C1 to C5 branched alkyl.

[13] 1. An aqueous composition for use in the decomposition of cellulose from a plant biomass source, said composition comprising: sulfuric acid, from 20 to 70 wt. % relative to the total weight of the composition; A compound containing an amine moiety and a sulfonic acid moiety selected from the group consisting of taurine; taurine derivatives; and taurine-related compounds; and Peroxide; Including, wherein the sulfuric acid and the amine-containing compound are present in a molar ratio ranging from 3:1 to 15:1.

[14] 1. An aqueous composition for use in the degradation of hemicellulose from a plant biomass source, said composition comprising: sulfuric acid, from 20 to 70 wt. % relative to the total weight of the composition; A compound comprising an amine moiety and a sulfonic acid moiety selected from the group consisting of taurine; taurine derivatives; and taurine-related compounds, Peroxide; wherein the sulfuric acid and the amine-containing compound are present in a molar ratio ranging from 3:1 to 15:1.

[15] The composition according to

[14] , wherein the compound comprising an amine moiety and a sulfonic acid moiety is selected from the group consisting of taurine and its derivatives, such as taurine-related compounds.

[16] The composition according to any one of [14 to

[15] , wherein the compound containing an amine moiety and a sulfonic acid moiety is taurine.

[17] The composition according to any one of [1] to

[16] , wherein the peroxide is hydrogen peroxide.

[18] 1. A method for delignification of plant biomass or biomass material, comprising the steps of: - providing said biomass material comprising cellulose fibers and lignin; - the biomass material required, 20-70 wt.% of sulfuric acid based on the total weight of the composition; A compound containing an amine moiety and a sulfonic acid moiety selected from the group consisting of taurine; taurine derivatives; and taurine-related compounds; and a peroxide; for a time sufficient to remove substantially all of the lignin present on the biomass material; The method comprising:

[19] The method of

[17] , wherein the taurine derivative or taurine-related compound is selected from the group consisting of sulfamic acid; taurolidine; taurocholic acid; tauroserucholic acid; tauromustine; 5-taurinomethyluridine and 5-taurinomethyl-2-thiouridine; homotaurine (tramiprosate); acamprosate; and taurates; and aminoalkylsulfonic acids in which alkyl is selected from the group consisting of C1-C5 straight chain alkyl and C1-C5 branched alkyl.

[20] The method of any one of

[18] and

[19] , wherein the sulfuric acid and the compound comprising an amine moiety and a sulfonic acid moiety are present in a molar ratio of 3:1 or greater.

[21] The method according to any one of

[18] to

[20] , wherein the peroxide is hydrogen peroxide.

Claims

1. Sulfuric acid; A compound comprising an amine moiety and a sulfonic acid moiety; and Peroxides, A modified aqueous acid composition comprising: wherein sulfuric acid and the compound comprising an amine moiety and a sulfonic acid moiety are present in a molar ratio of 1:1 or greater, The foregoing compositions, wherein the compound comprising an amine moiety and a sulfonic acid moiety is selected from the group consisting of taurine; taurolidine; taurocholic acid; tauroserucholic acid; tauromustine; 5-taurinomethyluridine and 5-taurinomethyl-2-thiouridine; homotaurine (tramiprosate); acamprosate; and taurates; and aminoalkylsulfonic acids, wherein alkyl is selected from the group consisting of C1-C5 straight chain alkyl and C3-C5 branched alkyl.

2. 10. The modified aqueous acid composition of claim 1, wherein sulfuric acid and said compound containing an amine moiety and a sulfonic acid moiety are present in a molar ratio of 15:1 or less.

3. Sulfuric acid; A compound comprising an amine moiety and a sulfonic acid moiety; and Peroxides, A denatured acid composition comprising: wherein sulfuric acid and the compound containing an amine moiety and a sulfonic acid moiety are present in a molar ratio of 3:1 or greater, The foregoing compositions, wherein the compound comprising an amine moiety and a sulfonic acid moiety is selected from the group consisting of taurine; taurolidine; taurocholic acid; tauroserucholic acid; tauromustine; 5-taurinomethyluridine and 5-taurinomethyl-2-thiouridine; homotaurine (tramiprosate); acamprosate; and taurates; and aminoalkylsulfonic acids, wherein alkyl is selected from the group consisting of C1-C5 straight chain alkyl and C3-C5 branched alkyl.

4. The composition of any one of claims 1 to 3, wherein the linear alkyl is selected from the group consisting of methyl; ethyl; propyl; and butyl.

5. The composition of any one of claims 1 to 4, wherein the branched alkyl is selected from the group consisting of isopropyl; isobutyl; and isopentyl.

6. The composition of any one of claims 1 to 5, wherein the compound containing an amine moiety and a sulfonic acid moiety is taurine.

7. 1. An aqueous composition for use in delignification of plant biomass, said composition comprising: 20 to 70 wt % of sulfuric acid, based on the total weight of the composition; Compounds containing an amine moiety and a sulfonic acid moiety, and Peroxides, The composition comprising: The foregoing compositions, wherein the compound comprising an amine moiety and a sulfonic acid moiety is selected from the group consisting of taurine; taurolidine; taurocholic acid; tauroserucholic acid; tauromustine; 5-taurinomethyluridine and 5-taurinomethyl-2-thiouridine; homotaurine (tramiprosate); acamprosate; and taurates; and aminoalkylsulfonic acids, wherein alkyl is selected from the group consisting of C1-C5 straight chain alkyl and C3-C5 branched alkyl.

8. 8. The composition of claim 7 for use in delignification of plant biomass, said composition comprising: 40 to 80 wt % of sulfuric acid, based on the total weight of the composition; Compounds containing an amine moiety and a sulfonic acid moiety; Including, the sulfuric acid and the compound comprising an amine moiety and a sulfonic acid moiety are present in a molar ratio ranging from 3:1 to 15:1, The foregoing compositions, wherein the compound comprising an amine moiety and a sulfonic acid moiety is selected from the group consisting of taurine; taurolidine; taurocholic acid; tauroserucholic acid; tauromustine; 5-taurinomethyluridine and 5-taurinomethyl-2-thiouridine; homotaurine (tramiprosate); acamprosate; and taurates; and aminoalkylsulfonic acids, wherein alkyl is selected from the group consisting of C1-C5 straight chain alkyl and C3-C5 branched alkyl.

9. 1. An aqueous composition for use in the decomposition of cellulose from a plant biomass source, said composition comprising: 20 to 70 wt % of sulfuric acid, based on the total weight of the composition; Compounds containing an amine moiety and a sulfonic acid moiety; and Peroxides; Including, the sulfuric acid and the compound comprising an amine moiety and a sulfonic acid moiety are present in a molar ratio ranging from 3:1 to 15:1, the compound comprising an amine moiety and a sulfonic acid moiety is selected from the group consisting of taurine; taurolidine; taurocholic acid; tauroserucholic acid; tauromustine; 5-taurinomethyluridine and 5-taurinomethyl-2-thiouridine; homotaurine (tramiprosate); acamprosate; and taurates; and aminoalkylsulfonic acids, wherein the alkyl is selected from the group consisting of C1-C5 straight chain alkyl and C3-C5 branched alkyl.

10. 1. An aqueous composition for use in the degradation of hemicellulose from a plant biomass source, said composition comprising: 20 to 70 wt % of sulfuric acid, based on the total weight of the composition; Compounds containing an amine moiety and a sulfonic acid moiety, and Peroxides; Including, the sulfuric acid and the compound comprising an amine moiety and a sulfonic acid moiety are present in a molar ratio ranging from 3:1 to 15:1, the compound comprising an amine moiety and a sulfonic acid moiety is selected from the group consisting of taurine; taurolidine; taurocholic acid; tauroserucholic acid; tauromustine; 5-taurinomethyluridine and 5-taurinomethyl-2-thiouridine; homotaurine (tramiprosate); acamprosate; and taurates; and aminoalkylsulfonic acids, wherein the alkyl is selected from the group consisting of C1-C5 straight chain alkyl and C3-C5 branched alkyl.

11. The composition of claim 10, wherein the compound comprising an amine moiety and a sulfonic acid moiety is taurine.

12. The composition according to any one of claims 1 to 11, wherein the peroxide is hydrogen peroxide.

13. 1. A method for delignification of plant biomass or biomass material, comprising the steps of: - providing said biomass material comprising cellulose fibres and lignin; - said biomass material requiring delignification, 20-70 wt. % of sulfuric acid, based on the total weight of the composition; A compound comprising an amine moiety and a sulfonic acid moiety; and a peroxide for a time sufficient to remove substantially all of the lignin present on the biomass material; The method comprising: the compound comprising an amine moiety and a sulfonic acid moiety is selected from the group consisting of taurine; taurolidine; taurocholic acid; tauroserucholic acid; tauromustine; 5-taurinomethyluridine and 5-taurinomethyl-2-thiouridine; homotaurine (tramiprosate); acamprosate; and taurates; and aminoalkylsulfonic acids, wherein alkyl is selected from the group consisting of C1-C5 straight chain alkyl and C3-C5 branched alkyl.

14. 14. The method of claim 13, wherein the sulfuric acid and the compound comprising an amine moiety and a sulfonic acid moiety are present in a molar ratio of 3:1 or greater.

15. 15. The method according to claim 13 or 14, wherein the peroxide is hydrogen peroxide.

Citation Information

Patent Citations

  • Sulfuric acid / hydrogen peroxide microetchant stabilizer and preparation method thereof

    CN101962775A

  • Deplating solution for removing nickel on cooper surface, preparation method thereof, and method for removing nickel on cooper surface

    CN103572306A

  • Environment-friendly stainless steel pickling agent free of nitrogen and phosphorus elements and application method thereof

    CN103820796A

  • Cleaning method of concentration system for wet process phosphoric acid purifying process

    CN109877097A

  • JP1974086225A